Challenges in evaluating Islamic education learning in schools: Implications for educational objectives - Arlinda, Arlinda Ayu Diah Arfani (Tadibia Islamika: Journal of Holistic Islamic Education, 2024)
This research was driven by numerous issues identified in the implementation of Islamic Religious Education (Pendidikan Agama Islam, hereinafter PAI) in schools, which diverge from the intended goals of Islamic education, particularly in fostering moral development and student skills. The primary objective of this study was to analyze the challenges in evaluating PAI learning in schools and to understand its implications for the overarching goals of Islamic education. Employing a qualitative approach, this study utilizes a descriptive-analytical method through library research. The data validity was established through the examination of various relevant sources, including journals, scholarly articles, books, and documents pertinent to the evaluation of PAI learning. The findings reveal significant problems, particularly in the neglect of affective and psychomotor domains, with an overemphasis on cognitive assessment. The assessment methods often fail to reflect the intrinsic values or spirituality, are inconsistent, and tend to be subjective. These issues manifest in the form of assessments that do not adequately capture the moral and ethical dimensions that are central to Islamic education. Consequently, these shortcomings hinder the achievement of the primary goals of Islamic education, which include the cultivation of exemplary moral character and the recognition of diverse student skills and abilities. Furthermore, the inconsistency and subjectivity in assessment practices undermine the reliability and effectiveness of the educational outcomes. Addressing these issues is crucial for aligning the evaluation methods with the holistic objectives of Islamic education, thereby ensuring a more comprehensive development of students' intellectual, moral, and practical competencies.